2017
DOI: 10.1038/s41598-017-14430-9
|View full text |Cite
|
Sign up to set email alerts
|

Combining 18F-FDG positron emission tomography with Up-to-seven criteria for selecting suitable liver transplant patients with advanced hepatocellular carcinoma

Abstract: The Up-to-seven (UTS) criteria (sum of tumor size and number not exceeding 7) for indicating liver transplantation (LT) in hepatocellular carcinoma (HCC) were originally based on explant pathology features and absence of microvascular invasion (MVI). 18F-fludeoxyglucose (18F-FDG) positron emission tomography (PET) was shown to indicate the risk of MVI and tumor recurrence. The aim of this study was to analyze the prognostic significance of the clinical UTS criteria when being combined with PET-status of the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…55 Some predictive models incorporating tumor biology in selection criteria combining tumor burden, biomarkers, and 18 F-FDG PET avidity have been reported in the LDLT setting, including the National Cancer Center Korea and Japanese criteria. 28,[56][57][58][59][60] One interesting aspect regarding selection criteria is that centers with longer wait times use downstaging/response to LRT by necessity whereas centers which primarily perform LDLT and have short wait times tend to have fairly liberal tumor burden criteria but rely heavily on biomarkers and/or negative 18 F-fluorodeoxyglucose positron emission tomography scan. FDG-negative patients beyond Milan criteria have satisfactory post-LT outcome 56,[58][59][60] whereas those with a tumor to nontumor ratio >2 tend to do poorly.…”
Section: Live Donor Lt For Hcc Selection Criteria/prediction Models Fmentioning
confidence: 99%
“…55 Some predictive models incorporating tumor biology in selection criteria combining tumor burden, biomarkers, and 18 F-FDG PET avidity have been reported in the LDLT setting, including the National Cancer Center Korea and Japanese criteria. 28,[56][57][58][59][60] One interesting aspect regarding selection criteria is that centers with longer wait times use downstaging/response to LRT by necessity whereas centers which primarily perform LDLT and have short wait times tend to have fairly liberal tumor burden criteria but rely heavily on biomarkers and/or negative 18 F-fluorodeoxyglucose positron emission tomography scan. FDG-negative patients beyond Milan criteria have satisfactory post-LT outcome 56,[58][59][60] whereas those with a tumor to nontumor ratio >2 tend to do poorly.…”
Section: Live Donor Lt For Hcc Selection Criteria/prediction Models Fmentioning
confidence: 99%
“…They concluded that PET/CT negative patients with HCC beyond MC might achieve excellent post-transplant disease-free survival (DFS). In a more recent study, they combined the pre-transplant 18F-FDG-PET/CT assessments with Up-to-seven criteria[ 60 ]. Among 116 patients with HCC who underwent 18F-FDG-PET/CT prior to LT, 5-year DFS was comparable between patients within Up-to-seven criteria ( n = 85) and those beyond Up-to-seven criteria with negative PET/CT ( n = 16) (81.0% vs 87.1%, P = 0.5).…”
Section: Correlation Between 18f-fdg Pet/ct and Morphological Criterimentioning
confidence: 99%
“…In a cohort of 116 liver transplant patients with HCC, Kornberg et al[ 60 ] reported a 5-year DFS rate of 93.3% in PET/CT negative patients vs 38.1% in PET/CT positive patients. PET/CT positive patients showed a recurrence rate of 58.5%, while only 6.7% of the PET/CT negative patients had recurrence.…”
Section: Role Of 18f-fdg Pet/ct In Predicting Post-transplant Hcc Recmentioning
confidence: 99%
“…In HCC, glucose metabolism is correlated with tumor grade and aggressiveness, which is assessed by 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT). Glucose metabolism was found to be a significant prognostic factor of survival in patients with hepatic tumors undergoing curative surgical resection (9).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to analyze the association between 18 F-FDG PET/CT metabolic burden indices or clinicopathological factors and the recurrence risk in patients with HCC, following OLT. The Deauville-like scoring system was used to classify the recurrence risk using the most important metabolic indices as the input factors.…”
Section: Introductionmentioning
confidence: 99%